ANALISIS DAYA DUKUNG TANAH PONDASI DANGKAL DENGAN BEBERAPA METODE - Martini, Martini (MEKTEK, 2009)
This analysis aim to obtain variation of bearing capacity of soil foundation for the same case based on methods is Terzaghi, Meyerhof, Vesic, Hansen and Ohsaki. And gets comparison of bearing capacity value from some the methods.Method Terzaghi and Ohsaki to have bearing capacity value of soil foundation which approximately equal. Method Hansen and Vesic also has value tending to same, only Meyerhof having different value x'self. For incline load, method Hansen, Vesic is tnding to same and just Meyerhof tending to value differs in. But method Hansen and Vesic at various foundation breadth ( B) at foundation square and circular that is B > 0,5 m happened decrease of bearing capacity of soil foundation and at B â‰¥ 1,5 m increases returns to its the value.